2021
DOI: 10.37394/232011.2021.16.15
|View full text |Cite
|
Sign up to set email alerts
|

Design Calculations of the Limiting Characteristics of Heat Pipes for Cooling Active Phased Antenna Arrays

Abstract: The article provides an algorithm for calculating the limiting characteristics of heat pipes for cooling active phased antenna arrays at a given saturation temperature. The maximum transmitted power is determined taking into account the limitations of the heat pipes operation by the capillary limit, by boiling (transition to film boiling, boiling limit), by the sonic limit at which the speed of steam reaches the speed of sound (sonic limit), by the entrainment of droplets liquid coolant from the surface of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 59 publications
0
1
0
Order By: Relevance
“…We use the spherical inclusion model to simulate the properties of the filled matrix [27][28][29][30][31][32][33][34][35][36]. Assuming that the reinforcing particles of fullerene carbon black are spheres.…”
Section: Characteristics Of the Obtained Compositesmentioning
confidence: 99%
“…We use the spherical inclusion model to simulate the properties of the filled matrix [27][28][29][30][31][32][33][34][35][36]. Assuming that the reinforcing particles of fullerene carbon black are spheres.…”
Section: Characteristics Of the Obtained Compositesmentioning
confidence: 99%
“…In the present paper a comparison of different indentation techniques of polymer coatings on steel substrates is carried out on the measurement results. Macro tests were previously conducted for the investigated coatings to determine the bending elastic modulus of coated steel substrates [7][8][9][10][11][12][13][14][15][16][17][18][19]. It was shown that the coatings, despite their small thickness, have a significant influence on the elastic properties of thin steel plate specimens.…”
Section: Introductionmentioning
confidence: 99%
“…And in papers [34][35][36][37][38] various mechanical investigations of heat protective composite materials on the basis of both analytical and numerical methods are given. Analytical solutions of thermoelasticity problems are important, including the validation of numerical solutions [39][40][41][42][43][44][45][46][47][48]. In this paper, we propose an analytical solution to the thermoelasticity problem for a plate heated by a source with a constant heat input at one surface.…”
Section: Introductionmentioning
confidence: 99%